(untitled) (Indian Journal of Psychology & Education, 2015)
Work roles can interfere with roles in the family domain and make people feel less satisfied with their job and also have a great impact on their general health. Sense of coherence seems to be an important way in which health is perceived in the recent years. This study explored the relationship between work-family conflict, job satisfaction, sense of coherence and general health among teachers. The sample consisted of 100 teachers including both men and women who are teaching in various colleges and universities in the Tamil Nadu and Puducherry. Work- family conflict scale by Netemeyer, Work satisfaction by Hackman, sense of coherence scale by Antonovsky and the general health scale by Goldberg were used for this study. The correlational analysis clearly indicates that there is a significant negative correlation between general health and sense of coherence and work satisfaction and a significant positive correlation between health and work- family conflict. Regression analysis shows that work family conflict and work satisfaction predict general health among teachers.